2013
DOI: 10.1186/1479-5876-11-307
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab mediates antibody-dependent cell-mediated cytotoxicity and phagocytosis to the same extent in both adjuvant and metastatic HER2/neu breast cancer patients

Abstract: BackgroundMonoclonal antibodies (mAb), such as trastuzumab are a valuable addition to breast cancer therapy. Data obtained from neoadjuvant settings revealed that antibody-dependent cell-mediated cytotoxicity (ADCC) is a major mechanism of action for the mAb trastuzumab. Conflicting results still call into question whether disease progression, prolonged treatment or concomitant chemotherapy influences ADCC and related immunological phenomena.MethodsWe analyzed the activity of ADCC and antibody-dependent cell-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 61 publications
(59 reference statements)
4
83
1
1
Order By: Relevance
“…The modulation of signaling pathways was also shown to be a major mechanism when cell lines were treated with trastuzumab, whereas ADCC was the leading mechanism in small animals treated with the same molecule (28,29). The mechanism of action involved was also shown to vary depending on the neoadjuvant or adjuvant setting, dose and administration schedule and the presence or absence of co-administered drugs (28,30,31). In 2004, Gennari et al showed that trastuzumab employed the preferential immunological mechanism of ADCC when used as a monotherapy and in a preoperative setting (28).…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of signaling pathways was also shown to be a major mechanism when cell lines were treated with trastuzumab, whereas ADCC was the leading mechanism in small animals treated with the same molecule (28,29). The mechanism of action involved was also shown to vary depending on the neoadjuvant or adjuvant setting, dose and administration schedule and the presence or absence of co-administered drugs (28,30,31). In 2004, Gennari et al showed that trastuzumab employed the preferential immunological mechanism of ADCC when used as a monotherapy and in a preoperative setting (28).…”
Section: Discussionmentioning
confidence: 99%
“…Ab-dependent cellular phagocytosis (ADCP) mediated by activated macrophages can kill tumor cells (14). It has been reported that trastuzumab could mediate ADCP against HER2-expressing cancer cells by PBMCs (15) and macrophages (16) in vitro. However, the role of macrophages in response to trastuzumab in antitumor efficacy has not been established in vivo.…”
mentioning
confidence: 99%
“…ADCP results from the binding of Abs to antigens on the surface of target cells and the binding of their Fc moieties to FcgRs on the surface of effector cells (11,18). There are more than five different isotypes of FcgRs, and the individual isotypes are expressed at various amounts on different effector cells involved in different effector functions (4 6).…”
Section: Discussionmentioning
confidence: 99%
“…Mogamulizumab, which is an anti-CC chemokine receptor 4 mAb that is defucosylated resulting in high affinity for FcgRIIIA, is anticipated to exert enhanced ADCC to kill tumour cells (9). Since the clinical effects of TRA involve ADCP as well as ADCC (10,11), modified TRA with enhanced effector functions is desired.…”
mentioning
confidence: 99%